Strange future pessimism and the 1992 Los Angeles riots - Song, Min 1970- (Duke University Press, 2005)
Introduction : when the strange erupts in culture -- Racial geography of Southern California -- The Black body in pain : Rodney King and strange days -- Culture of wounding : the riots and twilight -- Mourning Los Angeles -- A diasporic future? historical trauma and native speaker -- Epilogue : bearers of bad news
Includes bibliographical references (p. [257]-270) and index. - Includes filmography: p. [271]
Keywords: Race riots / History / 20th century / California / Los Angeles; Korean Americans / Social conditions / California / Los Angeles; African Americans / Social conditions / California / Los Angeles; Urban poor / Social conditions / California / Los Angeles; Race relations in literature; Ethnicity in literature; American literature / Korean American authors / History and criticism; Pessimism / Social aspects / United States